2016
DOI: 10.1007/s12034-016-1333-5
|View full text |Cite
|
Sign up to set email alerts
|

Sintering behaviour and microwave dielectric properties of a new complex perovskite: (1 − x)(Sr0.3Ca0.427Nd0.182)TiO3−x SmAlO3 ceramics

Abstract: Structural features and microwave dielectric properties of (1−x)(Sr 0.3 Ca 0.427 Nd 0.182 )TiO 3−x SmAlO 3 (0.05 ≤ x ≤ 0.4) ceramics were investigated. X-ray diffraction patterns illustrated that solid solutions with the orthorhombic perovskite were shown to be formed in the ranges of 0.05 ≤ x ≤ 0.4. Moreover, the dielectric constant (ε r ) of sintered ceramics had a quasi-linear decrease with the increase in SmAlO 3 content. A certain amount of Sm and Al substitution for A-and B-sites could substantially impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…For example, Suvorov et al [6] reported a new ceramics system with satisfactory microwave dielectric properties (ε r = 41, Q•f = 42000 GHz, and τ f = −18 ppm/℃) by mixing 0.65CaTiO 3 and 0.35SmAlO 3 and sintering them at 1450 ℃. Soon afterwards, a similar competitive composition of 0.66CaTiO 3 -0.34SmAlO 3 in this system was developed by Xu et al [7], displaying the best ε r and Q•f of 42.49 and 46069.86 GHz respectively when sintered at 1500 ℃ for 4 h. Comprehensive dielectric properties with ε r =58.3, Q•f=18800 GHz, and τ f = 2.3 ppm/℃, could be obtained in the ceramic 0.75(Sr 0.3 Ca 0.427 Nd 0.182 )TiO 3 -0.25SmAlO 3 after being sintered at 1500 ℃ for 4 h [8]. Solomon [9] revealed that the 0.1SmAlO 3 -0.9Ba(Zn 1/2 Nb 2/3 )O 3 composite, sintered at 1400 ℃ for 4 h, had ε r = 37, τ f =25 ppm/℃, and high Q•f.…”
Section: Introduction mentioning
confidence: 93%
“…For example, Suvorov et al [6] reported a new ceramics system with satisfactory microwave dielectric properties (ε r = 41, Q•f = 42000 GHz, and τ f = −18 ppm/℃) by mixing 0.65CaTiO 3 and 0.35SmAlO 3 and sintering them at 1450 ℃. Soon afterwards, a similar competitive composition of 0.66CaTiO 3 -0.34SmAlO 3 in this system was developed by Xu et al [7], displaying the best ε r and Q•f of 42.49 and 46069.86 GHz respectively when sintered at 1500 ℃ for 4 h. Comprehensive dielectric properties with ε r =58.3, Q•f=18800 GHz, and τ f = 2.3 ppm/℃, could be obtained in the ceramic 0.75(Sr 0.3 Ca 0.427 Nd 0.182 )TiO 3 -0.25SmAlO 3 after being sintered at 1500 ℃ for 4 h [8]. Solomon [9] revealed that the 0.1SmAlO 3 -0.9Ba(Zn 1/2 Nb 2/3 )O 3 composite, sintered at 1400 ℃ for 4 h, had ε r = 37, τ f =25 ppm/℃, and high Q•f.…”
Section: Introduction mentioning
confidence: 93%
“…Soon afterwards, a similar competitive composition of 0.66 CaTiO 3 -0.34SmAlO 3 in this system was found by Xu et al, displaying the best ε r and Q•f of 42.49 and 46069.86 GHz when sintered it at 1500 °C for 4 h [7]. The comprehensive dielectric properties with ε r = 58.3, Q•f = 18800 GHz and TCf = 2.3 ppm/•C could be obtained in the ceramic 0.75(Sr 0.3 Ca 0.427 Nd 0.182 )TiO 3 -0.25SmAlO 3 after being sintered at 1500 •C for 4 h [8]. Solomon revealed that the 0.1SmAlO 3 -0.9Ba(Zn 1/2 Nb 2/3 )O 3 composite sintered at 1400 •C for 4 h had ε r = 37, TCf = 25 ppm/•C and high Q•f [9].…”
Section: Introductionmentioning
confidence: 90%
“…Soon afterwards, a similar competitive composition of 0.66 CaTiO 3 -0.34SmAlO 3 in this system was developed by Xu et al, displaying the best ε r and Q•f of 42.49 and 46069.86 GHz when sintered at 1500 ℃ for 4 h [7]. Comprehensive dielectric properties with ε r =58.3, Q•f=18800 GHz, and τ f = 2.3 ppm/℃, could be obtained in the ceramic 0.75(Sr 0.3 Ca 0.427 Nd 0.182 )TiO 3 -0.25SmAlO 3 after being sintered at 1500 ℃ for 4 h [8]. Solomon revealed that the 0.1SmAlO 3 -0.9Ba(Zn 1/2 Nb 2/3 )O 3 composite, sintered at 1400 ℃ for 4 h, had ε r = 37, τ f =25 ppm/℃, and high Q•f [9].…”
Section: Introductionmentioning
confidence: 91%